A STUDY ON FACTORS CONSIDERED BY YOUNG CONSUMERS FOR THE PURCHASE OF ONLINE GAMES - 1. Ms. Deepali Chaudhary, 2. Prof. (Dr.) Avanish Kumar Tyagi (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
Globally, playing video games online has grown in popularity recently, particularly among young consumers. As a result, there is increased attention towards this section of the gaming industry. This paper is focused on determinants that play a role in influencing purchases of online games by young consumers. For this purpose, a sample of 100 respondents was collected in Delhi, and descriptive statistics and ANOVA were used for analysis.